PENGEMBANGAN MEDIA PEMBELAJARAN FIQIH BERBASIS MOTION GRAPIC TERHADAP PEMAHAMAN SISWA SEKOLAH DASAR DALAM MATERI WUDHU BERDASARKAN PENDEKATAN HADIST - Nurhamida, Lulu; Sa'adah, Barirotus; Lessy, Zulkipli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This library research aims to explore the potential of using motion graphic-based learning media to enhance elementary school students' understanding of wudu (ablution) based on Hadith approach. Education plays a crucial role in shaping a quality generation, and technological integration is key to enriching the learning experience. Motion graphics offer dynamic visual representations that effectively capture students' attention. Through comprehensive literature review, this study aims to provide a strong theoretical foundation for the development of motion graphic-based learning media. The research method involves identifying and analyzing relevant sources such as books, scholarly journals, and other related documents. By critically examining these literatures, this study aims to uncover best practices and theoretical frameworks that support the creation of effective motion graphic learning materials. This research contributes to the field of education by offering insights into the innovative use of technology to facilitate learning, particularly in the context of Fiqh education for elementary school students. Keywords: elementary school, hadist approach, learning media